Nanostructures for prevention, diagnosis, and treatment of viral respiratory infections: from influenza virus to SARS-CoV-2 variants - Esmaeel Sharifi; Satar Yousefiasl; Maria Trovato; Rossella Sartorius; Yasaman Esmaeili; Hamid Goodarzi; Matineh Ghomi; Ashkan Bigham; Farnaz Dabbagh Moghaddam; Maryam Heidarifard; Samiramis Pourmotabed; Ehsan Nazarzadeh Zare; et al. (Journal of Nanobiotechnology, 2023)
Abstract Viruses are a major cause of mortality and socio-economic downfall despite the plethora of biopharmaceuticals designed for their eradication. Conventional antiviral therapies are often ineffective. Live-attenuated vaccines can pose a safety risk due to the possibility of pathogen reversion, whereas inactivated viral vaccines and subunit vaccines do not generate robust and sustained immune responses. Recent studies have demonstrated the potential of strategies that combine nanotechnology concepts with the diagnosis, prevention, and treatment of viral infectious diseases. The present review provides a comprehensive introduction to the different strains of viruses involved in respiratory diseases and presents an overview of recent advances in the diagnosis and treatment of viral infections based on nanotechnology concepts and applications. Discussions in diagnostic/therapeutic nanotechnology-based approaches will be focused on H1N1 influenza, respiratory syncytial virus, human parainfluenza virus type 3 infections, as well as COVID-19 infections caused by the SARS-CoV-2 virus Delta variant and new emerging Omicron variant. Graphical Abstract